Cavernous hemangioma within a schwannoma: A case report of a rare amalgamation of two entities (Indian Journal of Case Reports, 2020)
Schwannoma occurring in peripheral nerves is a common tumor. Cavernous hemangiomas are also common vascular malformations. Although both of these lesions occur quite frequently, an amalgamation of both lesions is rare. Here, we present one such case. An adult male presented with a chief complaint of swelling over the left arm for 20 years. On histopathology, a diagnosis of schwannoma with cavernous hemangioma was made. A total of 36 cases have been reported in the literature, which showed cavernous hemangioma associated with neoplastic lesions of the nervous system; 24 cases were of Schwann cell origin. Furthermore, only 26 cases have been found in conjoint association. Overall, the association of cavernous hemangioma with neoplastic lesions of the nervous system is rare.